Language variation of sticker usage among students on whatsapp - Hesty Hasyim; Gusnawaty Gusnawaty; Ikhwan M. Said (Journal of Education, Social & Communication Studies, 2024)
In the era of digital communication, WhatsApp stickers have become a commonly used tool for conveying subtle expressions. This study investigates language variations in WhatsApp stickers among students. This qualitative research focuses on linguistic features in WhatsApp stickers used by students. Data were obtained from linguistic student groups, particularly those in the first and second semesters of 2023. Findings reveal diverse language variations across lexical, grammatical, orthographic, code-switching, and semantic features. The stickers showcase non-formal language, emphasizing innovative linguistic strategies and a high level of language proficiency. The use of stickers is characterized by interactive communication within WhatsApp groups, offering a visual alternative on small smartphone screens. In addition to serving as a form of self-expression, stickers also play a strategic role in fostering emotional connections and achieving specific communicative goals.